Pengaruh Kondisi Proses Terhadap Yield dan Kadar Lignin Pulp dari Pelepah Sawit dengan Proses Asam Formiat - Zulfansyah, Zulfansyah; Fermi, Muhammad Iwan; Amraini, Said Zul; Rionaldo, Hari; Utami, Meilany Sri (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Formic acid pulping of oil palm frond was conducted to study the influence of process variables (formic acid concentration, hydrogen peroxide concentration, and pulping time) on the properties of pulp produced (yield pulp and lignin content). A second order polynomial model consisiting of three independent process variables was found to accurately describe the formic acid pulping of oil palm frond. The propose equations reproduce the experimental results for the dependent variables with erros less than 5% for both yield dan lignin content. The most influential factor on yield pulp was formic acid concentration. Whereas, the cooking time has greater influence on lignin content.Keywords: formic acid, lingocelulose, pulping, pulp organosolv, oil palm fronds